EDUCATION IN CAMBODIA: WOMEN’S PERSPECTIVE TOWARDS EDUCATION INSAVY KHLEANG - IHWANI, SITI SUHAILA; MUHTAR, ADIBAH; MUSA, NORHAFIZAH; RASHID, MOHD HAMBALI; HEHSAN, AMINUDDIN; RASHID, ZETTY NURZULIANA; ZAILANI, ROZIANA (Human Sustainability Procedia, 2018)
Education system in Cambodia is in the process of rebuilding towards community. Over the last decade,progresses have been madeto improvethe education in enhancing family life.Cham Muslim women in Savy Khleang struggle to survive and nurture their children. This paper will examine perspectiveof Cham Muslim women with a focus on education. This paper also identifies the implication of education into womenlife